Probiotics: Comprehensive Exploration of the Growth Promotion Mechanisms in Shrimps - Joanna Xuan Hui Goh; Loh Teng-Hern Tan; Jodi Woan-Fei Law; Kooi-Yeong Khaw; Gokhan Zengin; Kok Gan Chan; Vengadesh Letchumanan; Learn-Han Lee; Bey-Hing Goh (Progress in Microbes and Molecular Biology)
As feed accounts for a significant proportion of a farm’s expenditure, animal nutrition is one of the key profit determinants. Attributed to the size-dependent market value, enhancing shrimps' growth is essential to maximize profit. Despite not being the best option, antibiotics are often used as growth-promoting agents in farming. Although this trend is less explicit in aquaculture, increasing production yield is paramount, especially when intensive aquafarming compromises animal growth and increases disease prevalence. However, the environmental and clinical pitfalls of indiscriminate antibiotic usage are surfacing. Fortunately, increasing evidence demonstrated probiotics as a safer, more sustainable, and environmental-friendly substitute for antibiotics. Nonetheless, most studies are observational, and the growth-promotion mechanisms of these agents are yet to be elucidated. In this light, this review aims to decipher the growth promotion mechanisms of probiotics in shrimps based on the primary works conducted. Evidently, probiotic treatment modulates the gut microbiome composition. The growth promotion effect of probiotics is partly mediated through the production of bioactive compounds such as short-chain fatty acids, vitamins, and polyamines. Besides, elevated digestive enzyme activities following the introduction of probiotics may help enhance digestibility and utilization. Histological changes at the hepatopancreas and intestine were evident. Furthermore, probiotics may reinforce the protective mechanisms in the gut and strengthen immune function. Treated shrimps demonstrate better appetite and exhibit superior metabolic and growth-related genes profile. Contrasting these recognized mechanisms with antibiotics helps construct the initial framework for designing high-quality probiotics for growth enhancement in farmed animals.